The Federal Democratic Republic of Ethiopia : Poverty Reduction Strategy Paper: Joint Staff Advisory Note on the Growth and Transformation Plan 2010/11: 2014/15. (IMF Staff Country Reports; Country Report ;, 2011)
Ethiopia's growth and transformation plan (GTP) for the periods 2010/2011 and 2014/2015 is reviewed by the joint staff advisory note has been discussed in this study. The macroeconomic framework designed to improve the GTP's growth is outlined. The priority actions and critical areas for pro-poor growth taken by the government are discussed in detail. Implementation of framework, monitoring, and evaluation is also outlined.